INVENTARISASI JENIS TUMBUHAN YANG BERPOTENSI MENINGKATKAN KETAHANAN PANGAN DI KEPULAUAN SPERMODE SULAWESI SELATAN - Priosambodo, Dody (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
The Spermonde Islands are a group of small islands off the west coast of South Sulawesi that have characteristics of rich coastal and marine ecosystems, but are vulnerable to climate change pressures and limited food resources. This study aims to identify local plant species that have the potential as alternative food sources to support community food security on these small islands. The method used was an exploratory survey with a participatory approach, involving local communities on five selected islands. The inventory results showed thatthere were 31 types of potential food plants, including tubers, local fruits, vegetables, and wild plants that could be used as sources of carbohydrates, vegetable protein, and micronutrients. Several species such as Artocarpus altilis (breadfruit), Moringa oleifera (moringa), and Pandanus tectorius (sea pandan) have high nutritional value and good ecological adaptation. This study recommends the utilization and preservation of local plants as a strategy to strengthen small island-based food security. Kata kunci : food security, local plants, small islands, spermonde islands, biodiversity